Optimizing the use of SMDS biosludge compost as a soil fertilizer-conditioner : effects on soil structure - Anita, ak Muda. (Universiti Malaysia Sarawak (UNIMAS), 2005)
A study was conducted to investigate the extent by which soil aggregation is affected by SMDS compost application. The mixture of silt clay loam soil and sandy soil in the ratio of 2: 1 was mixed with compost to give mixtures containing 0%,5%,20% and 50% compost by volume and incubated for two weeks. Soil aggregation was significantly affected by different rates of compost. For size fraction of 5 -10 mm, % aggregation was highest with the 20% compost. For size fraction of 2 -5 mm, % aggregation was highest with the 5% compost. Higher percentage of the smaller aggregate size fractions (1.18 -2 mm, 0.6 -1.18 mm, 0.3 -0.6 mm and 0 -0.3 mm size range) was obtained with the 50% of compost level. Mean weight diameter (MWD) was used to measure the degree of soil aggregation for the different treatments. MWD increased with increasing amounts of compost applied up to 20% but decreased at 50% compost level. This shows that very high amounts of compost could not develop soil aggregates within short period of incubation. Overall SMDS compost was effective in improving soil structure and has good conditioner value.